Simulation of the impact of land use change on surface run-off in Karst Leang Lonrong Sub-Watershed - Wahyullah Wahyullah; Hendrayanto Hendrayanto; Yuli Suharnoto (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Estimation of surface run-off in karst watersheds has not been widely carried out and the estimation method is generally developed for non-karst watersheds. This study aims to analyze the accuracy of estimation of river discharge at the outlet of the Karst Biringere Sub-watershed using the modified Soil Conservation Service Curve Number (SCS-CN) method and analyzed the impact of land use change on river discharge at the outlet of the Karst Biringere Sub-watershed. Modification of the SCS-CN method in estimating direct flow at the outlet of the Beringere Sub-watershed is influenced by the similarity of rainfall and direct flow fluctuation of river discharge. The modified SCS-CN method provides satisfactory direct flow estimation when rainfall with observed direct flow of river discharge forms a linear relationship with a strong correlation. Changes in land use with reduced forest cover into mining areas result in increased run-off and reduced storage, the larger the forest land becomes mining areas, the greater the increase in run-off and reduction in storage. Reclamation of the former mining area to be a forest reduces run-off and increases water storage.